The Effect of Washing Procedures on Contamination of Raw Vegetables with Nematodes Larvae - Elahi, Dr. Razieh (Asian Journal of Pharmaceutics (AJP), 2018)
Background and Objective: Vegetables can be contaminated with bacteria, viral, and parasitic pathogens during their cultivation, collection, and transportation processes, and consumption of unsafe vegetables is considered a risk factor for human parasitic infections. This study aimed to evaluate the contamination of raw vegetables with nematodes larvae, and the effect of washing procedures on their elimination in Shahrekord city, Iran. Materials and Methods: This study carried out on 160 samples of different vegetables including mint, basil, garden cress, parsley, satureja, radish, chives, and wild leek. Each sample was divided into four groups including unwashed and washed with pure water, vinegar, and germicide groups. Then, the samples were examined for nematodes larvae using Baermann funnel technique. Data were analyzed using Chi-square test. Results: Among 40 samples on each group, contamination was detected in 33 (82.5%) of unwashed group, 13 (32.5%) of washed with pure water group, five (12.5%) of washed with vinegar, and two (0.5%) of washed with germicide group. There was a significant difference in the rate of contamination in the washed groups compared to the control group (P < 0.05). Contamination rate in the group washed with water was significantly higher than the vinegar and germicide groups (P < 0.05) Moreover, our study showed that the highest rate of contamination was in chives and wild leek and the lowest one in radish. Conclusion: This study concluded that vegetables could be a potential source of nematodes larvae and proper washing and disinfecting procedures before consumption of raw vegetables should be performed to avoid transmission of nematodes larvae.